Controlling of Water Collection Ability by an Elasticity‐Regulated Bioinspired Fiber. Issue 5 (19th January 2015) - Wang, Sijie; Feng, Shile; Hou, Yongping; Zheng, Yongmei
<x xml:space="preserve">Abstract</x> A special artificial spider silk is presented which is fabricated by using both an elastic polymer and a fiber, and the water collection behavior is investigated. Through exerting tension in varying degree, the length of the three‐phase contact line (TCL) and the area of spindle knot can be regulated readily, which makes a great contribution to the improvement of collecting efficiency and water‐hanging ability. The water‐hanging ability can be predicted at a given stretching ratio according to the given expression of the TCL. As a result, liquid capture or release of distinct measure can be achieved via exerting tension. This research is helpful to design smart materials for developing applications in fogwater collection, dehumidification, high‐efficiency humidity control, and controllable adhesion. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>